Google News returns to Spain: challenges and opportunities for professionals and academics - Lopezosa, Carlos (Anuario ThinkEPI, 2022)
The Google News Spain service has been relaunched after 8 years owing to the approval in Congress of the European copyright directive that allows Spanish media to make their own decisions on how to monetize and discover their content. This paper aims to present a review of the challenges and opportunities that the return of Google News Spain represents for professionals in the journalistic sector as well as for academics and scholars of communication, documentation, and web visibility. To this end, an analysis of the operation and new services of Google´s news aggregator is carried out.